Multi-period investment strategies under cumulative prospect theory - Liurui Deng; Traian A. Pirvu (Journal of Risk and Financial Management, 2019)
In this article, inspired by Shi et al., we investigate the optimal portfolio selection with one risk-free asset and one risky asset in a multiple period setting under the cumulative prospect theory (CPT) risk criterion. Compared with their study, our novelty is that we consider a stochastic benchmark and portfolio constraints. By performing a numerical analysis, we test the sensitivity of the optimal CPT investment strategies to different model parameters.
Keywords: 330; cumulative prospect theory; portfolio selection; multi-period investment strategy